2008
DOI: 10.1139/f08-082
|View full text |Cite
|
Sign up to set email alerts
|

Nature and nurture in dormancy: dissolved oxygen, pH, and maternal investment impact Bythotrephes longimanus resting egg emergence and neonate condition

Abstract: Bythotrephes longimanus (Onychopoda: Cercopagidae), an invasive zooplankter in North America, requires suitable habitat to satisfy its planktonic and resting stages, which occupy the pelagia and sediment of lakes, respectively. Thousands of resting eggs from hundreds of planktonic mothers were exposed to laboratory conditions that mimicked gradients observed in lake sediment (dissolved oxygen = 1.4-11.9 mgÁL -1 ; pH = 3-11). Eggs hatched in all treatments, which confirms the utility of dormancy and the robustn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 61 publications
2
28
1
Order By: Relevance
“…Once counted, resting eggs were transferred into environmental growth chambers. Hatching experiments were conducted in the laboratory in order to facilitate monitoring, using established methodology for hatching Bythotrephes resting eggs (Brown 2008). Resting eggs were placed in jars covered by 100 lm mesh in groups of 10.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once counted, resting eggs were transferred into environmental growth chambers. Hatching experiments were conducted in the laboratory in order to facilitate monitoring, using established methodology for hatching Bythotrephes resting eggs (Brown 2008). Resting eggs were placed in jars covered by 100 lm mesh in groups of 10.…”
Section: Data Collectionmentioning
confidence: 99%
“…The aquaria were stored at 48C in the dark for four months to simulate overwintering conditions in lakes. After this period, the temperature in the chamber was raised to 6.58C to promote hatching (Brown 2008). Hatching was monitored weekly for four months and the percentage of eggs hatched from each enclosure that had produced resting eggs was calculated.…”
Section: Data Collectionmentioning
confidence: 99%
“…Similar effects of anoxia were observed also in Artemia (Clegg, 1997). We are not aware of any reports showing the inhibitory effect of anoxia on the hatching of cladoceran dormant eggs, but we expect there to be one, as it was proven that incubation in water with higher oxygen concentrations results in higher hatching rates from Daphnia magna (De Meester, 1993) and Bythotrephes longimanus (Brown, 2008) dormant eggs than incubation in water of low oxygen content. Moreover, Carvalho and Wolf (1989) suggested that anoxic conditions can prolong diapause in Daphnia.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from other studies suggests that reservoirs tend to have larger watershed-area : lake-volume ratios than natural lakes and this may be one factor contributing to their productivity (Havel et al 2005). Increased food availability may facilitate not only larger populations that are less vulnerable to Allee effects but may also permit more expansive in-lake dispersal of planktonic and resting stages (Brown 2008), which could improve survivorship and enhance establishment success. Associations between species establishment success and periods or locations of surplus resource availability have been demonstrated widely in terrestrial plants (Davis et al 2000).…”
Section: Discussionmentioning
confidence: 99%